Fine needle aspiration biopsy in the diagnosis of intraocular mass lesions - Shanmugam Mahesh; Biswas Jyotirmay (Indian Journal of Ophthalmology, 1997)
Fine needle aspiration biopsy (FNAB) was done in 5 patients who reported with atypical clinical presentation of intraocular tumour. The procedure was useful in 4 out of 5 cases and was without complications. With close co-operation between ophthalmologist and pathologist, FNAB is an useful adjunct for accurate diagnosis in selected patients.